Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1242/jcs.133108
|View full text |Cite|
|
Sign up to set email alerts
|

ERM proteins in cancer progression

Abstract: Members of the ezrin–radixin–moesin (ERM) family of proteins are involved in multiple aspects of cell migration by acting both as crosslinkers between the membrane, receptors and the actin cytoskeleton, and as regulators of signalling molecules that are implicated in cell adhesion, cell polarity and migration. Increasing evidence suggests that the regulation of cell signalling and the cytoskeleton by ERM proteins is crucial during cancer progression. Thus, both their expression levels and subcellular localisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
152
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(166 citation statements)
references
References 130 publications
(150 reference statements)
6
152
0
1
Order By: Relevance
“…The ERM family is composed of the proteins Ezrin, Moesin and Radixin which are thought to be a cross-linker between plasma membranes and actin-based cytoskeleton and subsequently participate in regulation of cell motility [16]. In the present study, Moesin expression was found decreased in the membrane and increased in the cytoplasm during the malignant transformation of oral epithelia, and cytoplasmic overexpression of Moesin correlated with nodal metastasis and poor prognosis of OSCCs, which was consistent with previous studies [17,18].…”
Section: Discussionsupporting
confidence: 92%
“…The ERM family is composed of the proteins Ezrin, Moesin and Radixin which are thought to be a cross-linker between plasma membranes and actin-based cytoskeleton and subsequently participate in regulation of cell motility [16]. In the present study, Moesin expression was found decreased in the membrane and increased in the cytoplasm during the malignant transformation of oral epithelia, and cytoplasmic overexpression of Moesin correlated with nodal metastasis and poor prognosis of OSCCs, which was consistent with previous studies [17,18].…”
Section: Discussionsupporting
confidence: 92%
“…It is well known that protein tyrosine phosphatases possessing an ERM domain belong to FERM (band four-point-one, ezrin, radixin, moesin homology) domain family known as PTPL1/PTP-BAS protein. This band 4.1/FERM domain consists of an actin binding, peptide binding and phosphatidyl inositol phosphate binding motif [14]. Four out of the above 16 peptides showed significant similarity to the putative B. malayi PTPL protein.…”
Section: Discussionmentioning
confidence: 97%
“…in). It has been reported that FERM domains when bound to PtsdIns (4,5)P2 at plasma membrane are phosphorylated by specific kinases leading to unfolding of the F-actin domain, thereby exposing it to link with the varied cytoskeletal and transmembrane proteins such as Rho GTPases, Wnt-bcatenin, cadherin and Akt kinases [14]. Thus, the presence of FERM domain containing proteins is often associated with the presence of different transmembrane and cytoskeletal proteins like actin.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins both directly provide the link between actin cortex and plasma membrane through their ability to interact with trans membrane proteins and the underlying cytoskeleton and also can regulate the activities of signal transduction pathways responsible for cell polarity and migration [146]. It was shown that moesin participates in formation of membrane underlying actin cortex in non polarized rounded lymphocytes and is accumulated in their tail region during migration (lymphocytes move using amoe boid motion) [147].…”
Section: Mesenchymal-amoeboid Transitionmentioning
confidence: 99%